Dynamics of students' physical fitness during sectional crossfit and football sessions - Valeriy Hrygoriev (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to assess the influence of crossfit and football in the sectional work on physical education on the dynamics of physical fitness of students. Material & Methods: studies of the level of physical preparedness of students were carried out with the help of two tests before and after the introduction of experimental techniques in the survey groups. Two experimental (18 girls, 16 boys) and two control groups (22 girls and boys) from the 2nd year students of the Kherson State University. Results: the analysis of the physical readiness of the students of the University was carried out under the influence of the classes of crossfit and football in the framework of the sectional work on physical education on the dynamics of the indicators of the development of high-speed, strength and speed-strength qualities, the development of agility and flexibility. Conclusion: use of developed methodological approaches to the application of sectional forms of physical education contributed to significant changes in the indicators of physical preparedness.